Dual-purpose cooling plate for thermal management of prismatic lithium-ion batteries during normal operation and thermal runaway. (September 2019) - Mohammed, Abdul Haq; Esmaeeli, Roja; Aliniagerdroudbari, Haniph; Alhadri, Muapper; Hashemi, Seyed Reza; Nadkarni, Gopal; Farhad, Siamak
Highlights: A new duel-purpose cooling plate is designed for lithium-ion battery packs. This cooling plate can keep the battery below 25 °C during normal operation. This cooling plate can keep the battery at 75 °C in 30 s during thermal runaway. The coolant pressure-drop in cooling plate is 75 Pa during normal operation. The coolant pressure-drop in cooling plate is 54 kPa during thermal runaway. Abstract: A dual-purpose cooling plate for prismatic lithium-ion batteries (LIBs) to increase the battery pack life and safety for applications in vehicles, aircraft, and stationary electric storage systems for grid and renewables is proposed. The proposed cooling plate can maintain the temperature of the battery within the manufacturers' recommended temperatures during the battery normal operation to increase the battery life, and can effectively control and dissipate the generated heat during thermal runaway to prevent propagation of heat from one cell to the adjacent cells in the battery pack to increase the safety. The proposed cooling plate is made of aluminum and works on the principle of the liquid cooling method with 60% ethylene glycol in water as the coolant. The cooling plate is featured with pins with staggered arrangement, which act as heat sinks and disperse the coolant over the surface of the cooling plate. The performance of the cooling plate is examined for heat generation trend of aggressive discharging of the battery during the normal operation and the heat generation during thermal runaway of the fully charged battery. The results show that the designed cooling plate can maintain the LIB surface temperature below 25 °C with the input coolant temperature of 20 °C and flow rate of 0.2 L/min during the normal operation, and can control the LIB temperature during thermal runaway at about 75 °C in 30 s with the input coolant temperature of 20 °C and flow rate of 30 L/min. The pressure-drop of the coolant is also about 75 Pa for the normal operation mode and about 54 kPa for the thermal runaway operation mode of the cooling plate.